1993
DOI: 10.1254/jjp.63.433
|View full text |Cite
|
Sign up to set email alerts
|

Effects of KW-3635, a Specific Thromboxane A2-Receptor Antagonist, on the Development of Lupus Nephritis in NZB × NZW F1 Mice

Abstract: ABSTRACT-We examined the effect of KW-3635, a specific thromboxane A2 (TXA2)-receptor antagonist, on the development of lupus nephritis in NZB x NZW Fl mice. KW-3635 was orally given once a day for 33 weeks beginning at eight weeks of age. In the control group, the mice began to die at 39 weeks of age, show ing severe proteinuria and histopathologic abnormality in the renal glomeruli. Administration of KW-3635 (30 mg/kg/day) significantly reduced urinary protein excretion (1.7±0.9 vs. 8.5±2.4 mg/6 hr/mouse, P<… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

1994
1994
2011
2011

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 22 publications
1
2
0
Order By: Relevance
“…It is, therefore, possible that the high dose of KW-3635 might have completely inhibited even the beneficial action of TXA2 in the kidney, resulting in the bell-shaped effect of KW-3635. The present results are in accordance with our previous observation that chronic administration of KW-3635 (30 mg/kg/day) markedly attenuated the lupus nephritis in NZB X NZW F1 mice, whereas the high dose (100 mg/kg/day) of this drug did not improve the nephri tis (10).…”
Section: Introductionsupporting
confidence: 93%
“…It is, therefore, possible that the high dose of KW-3635 might have completely inhibited even the beneficial action of TXA2 in the kidney, resulting in the bell-shaped effect of KW-3635. The present results are in accordance with our previous observation that chronic administration of KW-3635 (30 mg/kg/day) markedly attenuated the lupus nephritis in NZB X NZW F1 mice, whereas the high dose (100 mg/kg/day) of this drug did not improve the nephri tis (10).…”
Section: Introductionsupporting
confidence: 93%
“…A TXA2 synthase inhibitor and a TXA2 receptor antagonist exerted an anti-nephritic effect on experimental nephritis in rats and a mouse lupus nephritic model, respectively (14)(15)(16). We reported that DP-1904, a TXA2 synthase inhibitor, improved the clini cal manifestations, although the treatment with DP-1904 was started after the nephritis had been established (17).…”
mentioning
confidence: 99%
“…A number of studies in animal models and in man published during the last 25 years have demon strated that TP-receptor antagonists and TS inhibitors reduce albuminuria and/or proteinuria, as well as urinary excretion of TxB 2 , the stable metabolite of TxA 2 [49,56, [63][64][65][66][67][68][69][70]. Therefore, antagonizing TP receptors and/or inhibiting TS may have the potential to be beneficial in proteinuric renal diseases.…”
Section: Role Of Txa 2 In Renal Proteinuriamentioning
confidence: 99%